Experimental Regulation to Address Modern Slavery and Forced Labour in Global Supply Chains: Canada's Passage of Transparency Modern Slavery Legislation - Humphrey, Jonelle (My University, 2024)
This thesis explores Canada’s regulatory response to modern slavery in global supply chains. It investigates the factors which influenced Canada to enact transparency modern slavery legislation. It also analyzes Canada’s strategy of utilizing multiple soft and hard law governance and regulatory techniques to strengthen its response to modern slavery. Using a theoretical framework which combines global governance and regulation literature with literature regarding the national institutionalization of global norms, this thesis examines how international actors that comprise the global anti-slavery network disseminate anti-slavery and corporate accountability norms. These norms are subsequently filtered through a country’s domestic political economy, and are translated into either transparency or mandatory human rights due diligence (MHRDD) legislation. The qualitative methods used in this thesis were documentary analysis and key informant interviews. Key informant interviews in conjunction with an analysis of relevant reports and parliamentary debates provided insight into the influences behind Canada’s enactment of various governance and regulatory techniques. Doctrinal legal analysis, and an assessment of the various techniques implemented in Canada, revealed the effectiveness of the individual techniques and how they interacted with each other. This thesis found that Canada adopted a transparency law due to a combination of: (1) International norm diffusion via an epistemic, global anti-slavery network; and (2) Canada’s unique domestic political economy. Features of Canada’s domestic political economy, including its affiliation as part of the Anglosphere, and its powerful mining industry, ultimately determined the enactment of transparency legislation. The thesis also found that Canada’s use of multiple, increasingly hard law governance and regulatory techniques is currently ineffective as these techniques do not complement each other, and actually weaken Canada’s regulatory response to modern slavery. Consequently, labour standards have not improved for supply chain workers. This thesis posits that Canada should prioritize centering and empowering workers to protect their own rights.
Keywords: Canada, transparency modern slavery legislation